2016
DOI: 10.1016/j.gaitpost.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of three cueing devices for people with Parkinson's disease with gait initiation difficulties

Abstract: Background-Freezing of gait (FOG) remains one of the most common debilitating aspects of Parkinson's disease and has been linked to injuries, falls and reduced quality of life. Although commercially available portable cueing devices exist claiming to assist with overcoming freezing; their immediate effectiveness in overcoming gait initiation failure currently unknown. This study investigated the effects of three different types of cueing device in people with Parkinson's disease who experience freezing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 28 publications
(34 reference statements)
4
58
0
1
Order By: Relevance
“…Cueing using laser shoes was associated with a significant reduction in the number and duration of FOG episodes, both "off" and "on" medication [160]. Besides, in McCandless et al's study, rhythmic tactile stimulation (pulsed vibration) was provided at an adjustable tempo of 10 to 280 beats/minute via a vibration clip attached anteriorly over the right side of the user's pelvis [161]. Results showed an immediate positive effect on the mean percentage of Off-FOG episodes during the walking task in 20 PD patients.…”
Section: Physiotherapymentioning
confidence: 99%
“…Cueing using laser shoes was associated with a significant reduction in the number and duration of FOG episodes, both "off" and "on" medication [160]. Besides, in McCandless et al's study, rhythmic tactile stimulation (pulsed vibration) was provided at an adjustable tempo of 10 to 280 beats/minute via a vibration clip attached anteriorly over the right side of the user's pelvis [161]. Results showed an immediate positive effect on the mean percentage of Off-FOG episodes during the walking task in 20 PD patients.…”
Section: Physiotherapymentioning
confidence: 99%
“…The use of a walking stick or a laser cane improves the forward/backward and side to side movements comparing to the use of a vibrating metronome [6,11]. Gait patterns of PD patients walking straight on a level ground without assistance were well investigated [2,4,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of research has demonstrated that individuals with PD can benefit from various cueing devices [ 6 , 7 , 8 ]. Individuals with PD increased their pedaling rate under auditory cueing (provided by a metronome) and visual cueing (presented as central road markers) conditions [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with PD can benefit from haptic (touch and proprioception) feedback to improve balance. Haptic cues from the use of a walking stick [ 11 ], and visual cues from a laser cane reduce forward/backward and side to side movements [ 6 ]. Gait patterns of PD patients walking straight on a level ground without assistance were well investigated [ 2 , 4 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%